Problems Faced and the Strategies Used in Teaching Science in English - Nurmaniza, Mansor (Universiti malaysia sarawak (UNIMAS), 2007)
This study was conducted to investigate the problems faced by primary schools teachers in Science in English. The research also aims to find out the strategies used by the Science teachers in overcoming the problems. A semi-structured interview was conducted to 20 teachers who teach Science in English. The findings showed that the respondents faced many problems in teaching Science in English. The main problems faced by the respondents were the students' proficiency level in understanding of the subject matter and in explaining concepts in English. The findings also revealed that respondents used several strategies in overcoming the problems.